Learning Motivation In Students Social Media Users At The Beginning Of The Offline Period - Anggara, Monica Novi; Widodo, Yohanes Heri (Universitas Sanata Dharma, 2023)
This study aims to: (1) Measure the learning motivation level of students who use social media at the beginning of the offline periods. (2) knowing the items on the learning motivation measurement scale that are identified as low can be proposed as guidance topics. This type of research is descriptive quantitative. The subjects of this study were 112 students who use social media in the guidance and counseling study program. Data collection uses a Likert scale with 49 valid items and has a Cronbach Alpha reliability index of 0.936. the scare is arranged based on aspects of learning motivation, namely: (1) Attention; (2) Relevance; (3) Confidence; (4) Satisfaction. The data analysis technique used in this study is descriptive statistics which refers to the categorization norms with very high, high, medium, low, and very low levels. The results of this study: (1) the learning motivation level of student’s social media users at the beginning of the offline period is high, in more detail 19.64% is in the very high category, 57.14% is in the high category, 22.32% is in the medium category, 0.90% with low category, and 0% with the very low category; (2) the results of item analysis show that 1 item has a low score. The proposed classical guidance topic is: 1) Tips to overcome learning boredom